ChemInform Abstract: Synthesis and Characterization of Cr4+‐Doped Ca2GeO4 Tunable Crystal. Issue 24 (June 2015) - Li, Chun; Xu, Jialin; Liu, Wang; Zheng, Dongyang; Zhang, Shanli; Zhang, Ying; Lin, Hai; Liu, Lina; Liu, Jinghe; Zeng, Fanming
Abstract: Ca2 GeO4 :Cr 4+ single crystals are prepared by the flux growth method from Cr2 O3, GeO2, and CaCO3 using CaCl2 as the flux, and characterized by XPS, near IR, visible absorption, and near IR luminescence spectroscopy.